2022
DOI: 10.1155/2022/6833959
|View full text |Cite|
|
Sign up to set email alerts
|

Dental 3D Printing Design Based on Neurodegeneration and Virtual Reality Imaging Technology

Abstract: Objective. To model and compare the stress variation and distribution of the implant and its supporting components under two types of loading with the abutment in the axial and coronal lingual augmentation positions by means of the 3D finite element method. Method. 15 all-ceramic crowns completed by the same technician between the years 2014 and 2015 were randomly selected. A high precision laser scanner was used to scan the specimen models of all-ceramic crowns and then converted and imported into the promapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The first virtual geographic environment teaching and research institute was established in Wuhan University's virtual reality laboratory, which enables a variety of technical equipment for 3D modeling. The Harbin Institute of Technology has similarly succeeded in simulating the movement of human facial muscles and various expression changes and other higher movements through virtual reality technology and has been studying the body language and other detailed dynamics produced by human speech, and can simulate synchronization techniques such as human voice and intonation [5][6][7]. Although scholars in major literature and cases have studied more about technology because it is recognized worldwide, art has likewise gradually surfaced from these technical aspects, and what has been studied by later generations is more about the artistry exhibited by the products of their predecessors [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The first virtual geographic environment teaching and research institute was established in Wuhan University's virtual reality laboratory, which enables a variety of technical equipment for 3D modeling. The Harbin Institute of Technology has similarly succeeded in simulating the movement of human facial muscles and various expression changes and other higher movements through virtual reality technology and has been studying the body language and other detailed dynamics produced by human speech, and can simulate synchronization techniques such as human voice and intonation [5][6][7]. Although scholars in major literature and cases have studied more about technology because it is recognized worldwide, art has likewise gradually surfaced from these technical aspects, and what has been studied by later generations is more about the artistry exhibited by the products of their predecessors [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%